PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERCACAT DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Chaidir, Chaidir (Universitas Pakuan, 2015)
ABSTRACTThe Firmâs Value is investorâs perception towards the companyâs success level which is often related tothe price of the stock. The high price of stock makes the value of the company high. The high FirmâsValue will make the market believe in not only the present condition of the company but also theprospect of the company. The purpose of this study was to examine the effect of Capital Structure,Profitability, and Company Growth simultaneosly / together and partially on the Firmâs Value. Periodof 2 years of research carried out during the year 2013-2014. This type of research is quantitative, themethode used purposive sampling. The analytical methode used is inferential statistics. The analyticalmethod using analytical tools that multiple linear regression analysis.The result is, The coefficient ofmultiple determination adjusted for adjusted R square = 0,670 means that 67 %. Firmâs Value isinfluenced by factors DAR, DER, ROE,ROA, Asset Growth and 33% is explained by other variabel.Result F test shows that simultaneosly DAR, DER, ROE, ROA and Asset Growth has significant effecton Firmâs Value. While t test show that partially DER, ROE and Asset Growth has significant positiveeffect on the Firmâs Value, variable DAR has negative effect on the Firmâs Value, and ROA has nosignificant effect on Firmâs Value.Keyword : DAR, DER, ROE, ROA, Asset Growth, dan PBV